2003
DOI: 10.1073/pnas.0737556100
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pathology and apoptotic muscle degeneration in Drosophila parkin mutants

Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder characterized by loss of dopaminergic neurons in the substantia nigra. Several lines of evidence strongly implicate mitochondrial dysfunction as a major causative factor in PD, although the molecular mechanisms responsible for mitochondrial dysfunction are poorly understood. Recently, loss-of-function mutations in the parkin gene, which encodes a ubiquitin-protein ligase, were found to underlie a familial form of PD known as autosomal recessive ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
1,069
3
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,121 publications
(1,122 citation statements)
references
References 34 publications
41
1,069
3
9
Order By: Relevance
“…In PD, identification of disease-specific genes that influence mitochondrial physiology, either directly or indirectly, have contributed greatly to our understanding of the role of mitochondrial impairment in the etiology of this disease [1,2]. For example, mitochondrial pathology and oxidative stress are prominent in Drosophila parkin null mutants, and are associated with degeneration of a subset of dopaminergic neurons in the brain [11,60,61]. Although nigral degeneration is absent in parkin-deficient mice, they exhibit decreased striatal mitochondrial respiratory capacity and decreased levels of proteins involved in protection from oxidative stress [12].…”
Section: Discussionmentioning
confidence: 99%
“…In PD, identification of disease-specific genes that influence mitochondrial physiology, either directly or indirectly, have contributed greatly to our understanding of the role of mitochondrial impairment in the etiology of this disease [1,2]. For example, mitochondrial pathology and oxidative stress are prominent in Drosophila parkin null mutants, and are associated with degeneration of a subset of dopaminergic neurons in the brain [11,60,61]. Although nigral degeneration is absent in parkin-deficient mice, they exhibit decreased striatal mitochondrial respiratory capacity and decreased levels of proteins involved in protection from oxidative stress [12].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in mitochondrial morphologyhave been also observed, but this led only to disruption of complex I function in nigral mitochondria and did not result in cell death [233]. Thus, mitochondrial defects and an increased susceptibility to oxygen radical damage were also reported in a parkin knockout model of Drosophila, suggesting that abnormalities in parkin ubiquitination function might be secondary in the course of pathogenic events [234,235]. In vitro studies of PARK2Ͳknockdown SHͲSY5Y neuroblastoma cell line showed apoptotic cell death and high levels of autoxidized forms of LͲ DOPA and dopamine, suggesting that parkin might have important antioxidant properties [236].…”
Section: Parkinmentioning
confidence: 97%
“…This difference may be due to the presence of CG12362, a recent duplicate of ariadne-1 (Marín and Ferrús 2002). On the other hand, parkin mutants are viable, although show some phenotype changes, caused by a general mitochondrial dysfunction (Greene et al 2003;Pesah et al 2004;Clark et al 2006;Park et al 2006;Yang et al 2006). For the other genes, there are no loss-offunction mutants described.…”
Section: Long-term Conservation Of Particular Rbr Genes and Functionamentioning
confidence: 99%